Optimization of the synchronous motor with hybrid permanent magnet excitation system. Issue 2 (2nd March 2015) - Knypiñski, Łukasz; Nowak, Lech; Demenko, Andrzej
Abstract : Purpose: – The purpose of this paper is to elaborate an algorithm and the software for the rotor structure optimization of the permanent magnet synchronous motor (PMSM) with a magnet composed of two materials made with the use of different technologies: sintered Neodymium magnets and powder dielectromagnets. To execute of optimization of selected motor structure using the non-deterministic procedure. Design/methodology/approach: – The mathematical model of the devices includes: the equation of the electromagnetic field, the electric circuit equations and equation of mechanical motion. The numerical implementation is based on finite element method and step-by-step algorithm. The genetic algorithm has been applied in the optimization procedures. The computer code has been developed. Findings: – The elaborated computer software has been applied for the optimization and design of PMSMs. The elaborated algorithm has been tested and a good convergence has been attained. The parameters of two optimal structures of PMSM motors have been compared. Originality/value: – The presented approach and computer software can be successfully applied to the design and optimization of different structure of PMSM with different type of rotors.